2021
DOI: 10.1155/2021/9939275
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial and Antibiofilm Activities of Copper Oxide Nanoparticles within Soft Denture Liners against Oral Pathogens

Abstract: Objectives. Soft denture liners provide a favorable environment for adhesion and colonization of microorganisms. This in vitro study aimed to examine the efficacy of different concentrations of copper oxide nanoparticles (CuO NPs) incorporation into soft denture liner on the biofilm formation of the microbial species. Methods. Field Emission Scanning Electron Microscopy (FESEM) images from NPs were recorded. Antifungal susceptibility testing of CuO NPs against five standard strains of Candida albicans (CBS 102… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 35 publications
(37 reference statements)
1
25
0
1
Order By: Relevance
“…Metal NPs in the 110 nm size range, in particular, has been demonstrated to have the most biocidal effect against bacteria (Shkodenko et al, 2020). The antibacterial characteristics of NPs were employed in the oral cavity to inhibit microbial adherence through two main mechanisms: mixing dental materials with NPs and covering surfaces with NPs, with the ultimate goal of decreasing biofilm development (Ansarifard et al, 2021). The research on using nanoparticles in orthodontics is few.…”
Section: Using a Thin Layer Of Nitrogen-doped Tio2 Nps To Coat An Ort...mentioning
confidence: 99%
“…Metal NPs in the 110 nm size range, in particular, has been demonstrated to have the most biocidal effect against bacteria (Shkodenko et al, 2020). The antibacterial characteristics of NPs were employed in the oral cavity to inhibit microbial adherence through two main mechanisms: mixing dental materials with NPs and covering surfaces with NPs, with the ultimate goal of decreasing biofilm development (Ansarifard et al, 2021). The research on using nanoparticles in orthodontics is few.…”
Section: Using a Thin Layer Of Nitrogen-doped Tio2 Nps To Coat An Ort...mentioning
confidence: 99%
“…The intrinsic porosity of soft denture pads facilitates the adhesion and colonization of microorganisms and promotes the formation of biofilms. A study by et al (200) showed that the incorporation of CuO NPs at a concentration of 500 µg/ ml into soft denture liners exerted an effective prevention of oral microbial infection. The biofilm inhibition rates of soft denture liners containing CuO NPs against C.albicans, Streptococcus sobrinus (S. sobrinus), S. mutans, and Streptococcus salivarius (S. salivariu) were 75%, 66%, 30%, and 60%, respectively.…”
Section: Soft Denture Linersmentioning
confidence: 99%
“…For the synthesis of copper oxide nanoparticles, ethanolic solutions of copper acetate and sodium hydroxide are used. They inhibit biofilm growth in soft denture liners in a dose-dependent manner [ 61 ].…”
Section: Nanoparticles With Antimicrobial Action Used In Dental Mater...mentioning
confidence: 99%
“…In a study of the antibiofilm activity of the self-cured acrylic-based GC Soft-liner containing CuO NPs in relation to the C. albicans biofilm, it was found that the material inhibits the growth of the C. albicans biofilm in a dose-dependent manner (in particular, up to 75% at a concentration of CuO NPs 500 μg mL −1 ) [ 61 ].…”
Section: Dental Implantology and Dental Prostheticsmentioning
confidence: 99%